2000
DOI: 10.1093/ps/79.5.689
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of partially hydrolyzed guar gum on infection of Salmonella enteritidis in young and laying hens

Abstract: The preventive effect of partially hydrolyzed guar gum (PHGG) on the colonization of Salmonella enteritidis (SE) in young and laying hens was investigated. The effects of feed supplemented with 0.025, 0.05, and 0.1% PHGG was examined on young hens orally infected with SE. The incidence of SE in organs was decreased, the excretion of SE into feces was increased, and the agglutinating antibody titer to SE in serum was decreased by the administration of PHGG to young hens. In particular, feed supplemented with 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 36 publications
0
29
0
2
Order By: Relevance
“…β-mannanase hydrolyzes β-1, 4-glycosidic bonds in β-mannans (Ooi and Kikuchi, 1995). Hydrolysis of guar gum galactomannan produces mannooligosaccharides which can improve growth performance of birds by inhibiting Salmonellae and E. coli colonization (Ishihara et al, 2000). It also decreases β-mannan levels in GI tract which increase stimulation of innate immune response as presented in Figure 2 ( Jackson et al, 2004).…”
Section: Methods To Improve the Nutritive Value Of Guar Mealmentioning
confidence: 99%
“…β-mannanase hydrolyzes β-1, 4-glycosidic bonds in β-mannans (Ooi and Kikuchi, 1995). Hydrolysis of guar gum galactomannan produces mannooligosaccharides which can improve growth performance of birds by inhibiting Salmonellae and E. coli colonization (Ishihara et al, 2000). It also decreases β-mannan levels in GI tract which increase stimulation of innate immune response as presented in Figure 2 ( Jackson et al, 2004).…”
Section: Methods To Improve the Nutritive Value Of Guar Mealmentioning
confidence: 99%
“…MOSs can also directly inhibit pathogenic microorganisms besides promoting the growth of probiotic microorganisms [7]. The inhibitory effects of oligosaccharides on pathogens are due to the direct interaction with human mucosal receptors and hence blocking of the bacterial binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effects of oligosaccharides on pathogens are due to the direct interaction with human mucosal receptors and hence blocking of the bacterial binding sites. Therefore, this process improved the elimination of these bacteria during excretion rather than their binding to mucosal receptors [7,8]. It has been reported that the fructo-oligosaccharides have a potential role as antitumorigenic agents; for example, fructo-oligosaccharides isolated from apple showed induced apoptosis in colon cancer cells and cell cycle arrest in S phase [9].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of oligosaccharides can, however, also be directly through interaction and hence blocking of the bacterial binding sites. This leads to the elimination of these bacteria with the digesta flow rather than their binding to mucosal receptors (Ishihara et al 2000;Naughton et al 2001;Spring et al 2000).…”
Section: Introductionmentioning
confidence: 99%